PENGARUH PROFITABILITAS, CORPORATE SOCIAL RESPONSIBILITY, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Filza Ilma; Kersna Minan; Ruswan Nurmadi (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2022)
This research aims to determine the effect of profitability, corporate social responsibility, and liquidity on firm value with capital structure as an intervening variable. This research used secondary data, which were financial reports from manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2015-2019. Sample selected by purposive sampling, from 31 companies with 5 years of observation were 155 data. The analysis method used path analysis. The results of this research showed that profitability had no significant effect on capital structure, corporate social responsibility and liquidity had a significant effect on capital structure, profitability and corporate social responsibility had a significant effect on firm value, liquidity and capital structure had no significant effect to firm value. And the capital structure is unable to mediate the relationship between profitability, corporate social responsibility, and liquidity on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from the period of 2015 to 2019.